Rabbit Production in Selected Urban Areas of Southern Ghana: Status and Implications for Policy and Research - Osei, DY; Apori, SO; Osafo, ELK (ANIMAL PRODUCTION, 2012)
A survey was conducted to elicit information on rabbit keeping in 26 urban areas of southern Ghana. The average age of the rabbit keepers was 44.3 years, and 95.5% of the keepers had formal education. Most of the producers got into rabbit keeping for money to meet urgent family needs, while household consumption was a major factor influencing the decision for rearing rabbits. Personal savings was the main source of income for the establishment of the rabbit enterprises. The major breeds of rabbits kept were the California White, New Zealand White and crossbreds of varied genetic variations. Backyard, small-scale and medium-scale commercial rabbit holdings were held by 18.2, 51.7 and 30.2% of the keepers respectively. The average rabbit population per farm was 77.8, with an average of 8.4 bucks, 21.6 does. Young rabbits formed 70.0% of the rabbit population. Owners of rabbitries usually cared for their animals as hired labour was expensive and often not available. High cost of feed was the most significant constraint to rabbit keeping, and mange was the most common disease affecting the rabbits. Marketing of rabbits was not organized, and this served as a disincentive to expanding the holdings. The rabbits were mostly sold either life or as fresh carcasses at the farm gate. To ensure a rapid growth of the rabbit industry, research should be undertaken to address the identified constraints to production while appropriate policies are put in place to enhance the growth of the industry.Keywords: rabbit keeping, socio-economic characteristics, farming technologiesÂ Animal Production 14(2):131-139